The Effects of HIV Mortality on Saving and Investment in Asia - Fawaz , Fadi; Frey, Eric; Piscitiello, Deborah (Asian Journal of Empirical Research, 2019)
This paper examines the effects of HIV/AIDS mortality on saving and investment in Asia. Annual data for years 1990-2015 from 43 Asian countries. The empirical model also allows for potential gender differences in AIDS mortality to vary the effect on savings and investment. Our research shows that there are gender and wealth differences in how this disease affects the macro economy. An increase in the AIDS mortality rate of either gender reduces saving and investment in low-income countries. In regards to savings, an increase in male AIDS mortality is shown to increase savings. On the other hand, an increase in female AIDS mortality is expected to decrease savings. In terms of investment we find the opposite effects across genders: increasing male AIDS mortality causes decrease in investment (though not statistically significant) and increasing female AIDS mortality increases investment. For low-income countries, we find a negative relationship between AIDS mortality of either gender on saving or investment.